A lightweight wearable biomechanical energy harvester. (16th June 2021) - Liu, Mingyi; Hill, Cherice; Queen, Robin; Zuo, Lei
Abstract: Human body energy harvesting has the potential to replace batteries to power wearable and mobile devices. However, the human body energy-harvester may impede human motion, be too heavy to carry, and increase the metabolic cost. In this paper, we present a lightweight device that generates electricity by harvesting energy from the negative muscle work of the human ankle and does not interfere with the natural motion of the human body. The energy harvester mounts on the leg and selectively engages to generate power in the terminal stance phase, during which the calf muscles are doing negative work. The engagement and disengagement are done by a simple but effective passive mechanism design. The modeling of the energy harvester was developed using the Lagrangian method and the energy-harvesting process was simulated to guide the device design, specifically choice between torsional stiffness, inertia, and damping terms for energy harvesting as well as human comfort. A test participant walking with the 100 g device on a treadmill at 4.8 km h −1 produced an average of 0.3 ± 0.05 W of electric power from the negative-muscle-work phase. Electromyography and torque measurement verified that the energy harvested comes from negative muscle work.